Analisis Kemampuan Literasi Baca Tulis pada Siswa Kelas IV SD 3 Wergu Wetan di Era Digital - Arfiasya Husna Zakiyya; Wihda Naifa Nabris Zilfa; Ariq Naqib Ma’ruf; Ahmad Fathir Muzaqi; Fina Fakhriyah; Erik Aditia Ismaya (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2026)
Reading and writing literacy is a fundamental competency that supports elementary school students’ learning success. However, the development of digital technology has changed students’ learning habits, with some students preferring gadgets over reading books. This study aims to analyze the reading and writing literacy skills of fourth-grade students at SD 3 Wergu Wetan in the digital era, identify factors influencing literacy skills, examine the impact of digital media use on literacy habits, and describe school efforts to strengthen literacy culture. This research employed a qualitative approach with a case study design involving fourth-grade teachers and students. Data were collected through observation, interviews, documentation, and questionnaires, then analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The results indicate that students’ literacy skills are categorized as fairly good, with a positive response percentage of 70.4%. Nevertheless, some students still require support in understanding reading materials and developing writing skills. Digital media influences literacy habits as both a challenge and an opportunity when used appropriately. School initiatives through the Wednesday Morning Literacy Program, visual-based learning media, and regular reading and writing activities contribute to strengthening literacy culture. Collaboration among schools, teachers, and parents is needed to optimize digital technology use while improving students’ literacy skills.